The Effect of Virtual Reality (VR) Intervention on Anxiety Levels and Quality of Life in Preoperative Patients Undergoing Spinal Anesthesia - Ica Lisnawati; Noor Khalilati; Candra Kusuma Negara (Indonesian Journal of Global Health Research, 2025)
Preoperative anxiety is a common psychological condition that can negatively affect patients' physiological responses and decrease their quality of life. Patients undergoing spinal anesthesia are particularly vulnerable, as they remain conscious throughout the procedure. Non-pharmacological interventions such as Virtual Reality (VR) offer an innovative approach to reducing anxiety; however, evidence of its effectiveness in regional hospital settings remains limited. This study aimed to examine the effect of Virtual Reality intervention on anxiety levels and quality of life among preoperative patients undergoing spinal anesthesia at Banjarmasin Regional General Hospital. A quasi-experimental design with a non-equivalent control group was employed. The sample consisted of 30 patients purposively divided into two groups: 15 in the intervention group and 15 in the control group. The intervention group received VR exposure for 20 minutes prior to surgery, while the control group received standard care. The instruments used were the Amsterdam Preoperative Anxiety and Information Scale (APAIS) and the Short Form-36 (SF-36) questionnaire. Data were analyzed using the Mann-Whitney and Wilcoxon Signed-Rank tests. Before the intervention, there were no significant differences between the intervention and control groups in anxiety scores (p = 0.614) or quality of life scores (p = 0.791). After the intervention, the intervention group showed a significant reduction in anxiety scores (13.8 ± 2.7) compared to the control group (20.1 ± 2.6) with a p-value of 0.004. A significant improvement was also observed in the quality of life scores of the intervention group (73.1 ± 6.4) compared to the control group (60.2 ± 7.3) with a p-value of 0.007. Virtual Reality intervention was effective in reducing anxiety and improving the quality of life of preoperative patients undergoing spinal anesthesia. VR has the potential to serve as a practical, efficient, and feasible non-pharmacological intervention in healthcare settings.